AN ANALYSIS OF FLEMING’S THEORY ON VARK (VISUAL, AURAL, READ/WRITE, AND KINESTHETIC) LEARNING STYLE IN COLLEGE STUDENTS - Riza Weganofa; Ayu Liskinasih; Siane Herawati; Indah Rustiani (Fakultas Bahasa dan Sastra Universitas PGRI Kanjuruhan Malang, 2022)
This study was aimed at investigating the kinds of learning style used by college students in learning English vocabulary. The researchers categorized the kinds of learning style based on Fleming’s theory into Visual (V), Aural (A), Read/Write (R), and Kinesthetic (K). Further, they used questionnaire and interview to collect the data from forty participants. The instruments were applied right after the participants finished their vocabulary course. The result of questionnaire shown that students used Kinesthetic (K) learning style for learning English in general. Meanwhile the result of the interview shown that learning style used by college students for learning English vocabulary was read/write (R) type. It can be concluded that most students used different learning styles for different purposes. The learning style can change over time according to the conditions that students need. Based on the stages of cognitive development, it can be said that college students included to adulthood which means they use abstract thought when they learnt something. They should have been able to understand the vocabulary by using visual learning style, since kinesthetic style is more suitable for children between 2 and 7 years of age than for adults. This indicates that between student’s beliefs and teacher’s beliefs are incompatible.